Treatment of Infected Pseudoarthrosis in a Subtrochanteric Fracture in a Patient with Osteopetrosis - Llano Lionel; Jorge D. Barla; Campelo Diego; Taype Danilo; Carlos F. Sancineto; Guido Carabelli (Case Reports in Orthopedics)
Osteopetrosis is a disease of osteoclasts that results in failure of bone remodeling. Despite the sclerotic radiographic appearance of the thickened cortices and its material hardness, osteopetrotic bone is weak and prone to fracture by minor trauma. We report a case of a subtrochanteric fracture in an osteopetrotic patient, with further pseudoarthrosis and infection. Several surgical procedures were required, with further complications. The outcome of each procedure and the final result are also described.